Selective photocatalytic decomposition of formic acid over AuPd nanoparticle-decorated TiO2 nanofibers toward high-yield hydrogen production - Zhang, Zhenyi (2014)
We present high-yield hydrogen production through selective photocatalytic decomposition of formic acid by using electrospun TiO2 nanofibers decorated with AuPd bimetallic alloy nanoparticles under simulated sunlight irradiation. By using only 5 mg of the AuPd/TiO2 nanofibers containing the 0.75% Au and 0.25% Pd, we could achieve an optimal H2 generation rate of 88.5 μmol h−1 with an apparent quantum yield at 365 nm as 15.6%, which is higher than that of the Pd/TiO2 and Au/TiO2 nanofibers by a factor of 1.6 and 4.5, respectively. The enhanced photocatalytic decomposition of formic acid for H2 generation could be attributed to the stronger electron-sink effect of AuPd alloy nanoparticles, the high selectivity of Pd for the dehydrogenation of formic acid, and the surface plasmon resonance effect of Au. More importantly, we demonstrate that the photocatalytic processes enable re-activation of the AuPd nanoparticles that were poisoned by CO during thermal decomposition of formic acid. As such, the presented AuPd/TiO2 nanofibers are promising materials for re-generation of H2 under mild conditions from liquid storage carrier of hydrogen.